2021
DOI: 10.3390/ijms22084249
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Gene Therapy Research in Polyglutamine Spinocerebellar Ataxias

Abstract: Polyglutamine spinocerebellar ataxias (PolyQ SCAs) are a group of 6 rare autosomal dominant diseases, which arise from an abnormal CAG repeat expansion in the coding region of their causative gene. These neurodegenerative ataxic disorders are characterized by progressive cerebellar degeneration, which translates into progressive ataxia, the main clinical feature, often accompanied by oculomotor deficits and dysarthria. Currently, PolyQ SCAs treatment is limited only to symptomatic mitigation, and no therapy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 121 publications
0
15
0
1
Order By: Relevance
“…The trinucleotide repeat disorders are also good candidates for AON targeting designed to downregulate toxic protein expression and reduce aggregation. In the case of SCA1, SCA2, SCA3 and SCA7 this has been investigated in mouse models where AONs delivered via intracerebroventricular injection reduced disease protein levels and improved phenotypes highlighting significant promise for AON therapy in this group of diseases [ 72–77 ]. For Huntington’s disease (HD), also a trinucleotide repeat disorder, multiple AONs designed to reduce the production of the huntingtin protein have been developed with promising results from early clinical trials [ 78–80 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The trinucleotide repeat disorders are also good candidates for AON targeting designed to downregulate toxic protein expression and reduce aggregation. In the case of SCA1, SCA2, SCA3 and SCA7 this has been investigated in mouse models where AONs delivered via intracerebroventricular injection reduced disease protein levels and improved phenotypes highlighting significant promise for AON therapy in this group of diseases [ 72–77 ]. For Huntington’s disease (HD), also a trinucleotide repeat disorder, multiple AONs designed to reduce the production of the huntingtin protein have been developed with promising results from early clinical trials [ 78–80 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…siRNA also holds promise for the many genetic diseases discussed above for AON therapy. For example, there are numerous studies on the development of siRNA for the SCAs using various experimental systems, of which siRNA for SCA3/Machado-Joseph disease (MJD) has seen the most extensive effort towards allele-specific gene silencing [ 72 ]. Similarly, there is extensive siRNA-based research in the ophthalmology field with several ongoing clinical trials for disorders such as glaucoma, dry eye syndrome, age-related macular degeneration and diabetic macular oedema [ 37 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…The downregulation led to 14-week prevention of oligomeric and nuclear accumulation of ATXN3 and rescued the motor impairment attributed to defects in Purkinje neuron firing frequency. Several other studies using siRNA and RNAi have also shown a successful and sustained reduction in ATXN3, with a recent review of them and other gene therapy approaches found in [175].…”
Section: Sca3mentioning
confidence: 99%
“…Although siRNA-and RNAi-based therapeutics can be classified as antisense technologies, this review will only focus on splice switching and RNaseH mechanisms in relation to the causative genes of SCAs. Various RNA-silencing and gene-therapy approaches have been recently reviewed [175].…”
Section: Antisense Therapeutics For Scasmentioning
confidence: 99%
“…The most common symptoms in SCA2 patients are motor ataxia and oculomotor dysfunction, with the slowing of saccades being a unique feature in SCA2 [ 6 ]. There is no cure for this disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%